Job satisfaction among employees at a statutory body: Lembaga Tabung Angkatan Tentera (LTAT) - Nurmaisara, Marudin (2019)
The purpose of the study is to determine factors such as, workload, salary and co-worker that can influence the job satisfaction among the staff of Armed Forces Fund Board (LTAT), Kuala Lumpur. Quantitative method was used, where a set of questionnaires were distributed by email and the response was 63.9% where 167 employees of LTAT answered the questionnaires. Data obtained was analysed using the SPSS software. It was tested using the reliability test for the questionnaires and descriptive analysis in order to get frequency, percentages and means. More importantly, based on the findings of the independent variable, salaries and co-workers have a positive relationship on job satisfaction but for variable workload does not positively relationship on job satisfaction. Hopefully the results of this study will help management identify factors to increase job satisfaction and work motivation among LTAT staff so that harmonious working environment can improve organizational productivity